2015
DOI: 10.1002/jmv.24322
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐28B polymorphisms and interferon gamma inducible protein‐10 serum levels in seronegative occult hepatitis C virus infection

Abstract: Polymorphisms upstream interleukin (IL)-28B gene and serum levels of interferon gamma inducible protein-10 (IP-10) are associated with spontaneous and treatment-induced hepatitis C virus (HCV) clearance. Patients with seronegative occult HCV infection are anti-HCV and serum HCV-RNA negative but have viral RNA in liver and abnormal values of liver enzymes. We examined if the rs12979860 polymorphism of IL-28B and serum IP-10 levels differ between chronic and seronegative occult CV infection. IL-28B polymorphism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
(52 reference statements)
2
9
1
Order By: Relevance
“…One probable explanation is that HCV has developed a number of evasion mechanisms, infection of PBMCs being one of those where the virus can avoid the immune defense system, while hepatocytes remain the actual target. Previous works demonstrated that patients with seronegative HCV have an HCV-specific cellular immune response with a probable immune surveillance function, suggesting that host immune response is able to control but not to eliminate, HCV replication in these cases (27). It may also be that the virus developed some new quasi-species in PBMC that showed delayed response to the antiviral therapy but we could not confirm that speculation now.…”
Section: Discussioncontrasting
confidence: 57%
“…One probable explanation is that HCV has developed a number of evasion mechanisms, infection of PBMCs being one of those where the virus can avoid the immune defense system, while hepatocytes remain the actual target. Previous works demonstrated that patients with seronegative HCV have an HCV-specific cellular immune response with a probable immune surveillance function, suggesting that host immune response is able to control but not to eliminate, HCV replication in these cases (27). It may also be that the virus developed some new quasi-species in PBMC that showed delayed response to the antiviral therapy but we could not confirm that speculation now.…”
Section: Discussioncontrasting
confidence: 57%
“…In contrast, Bartolomé et al . indicated that favorable IFNL3 rs12979860 was the most dominant genotype in patients with OCI . The reason why IFNL3 rs12979860 genotype is associated with OCI is unclear and its explanation requires further studies.…”
Section: Discussionmentioning
confidence: 97%
“…38 In contrast, Bartolomé et al indicated that favorable IFNL3 rs12979860 was the most dominant genotype in patients with OCI. 39 The reason why IFNL3 rs12979860 genotype is associated with OCI is unclear and its explanation requires further studies. However, several studies showed that IFNL3 rs12979860 non-CC genotypes related to higher ISG expression levels in the setting of CHC infection were previously correlated with lower levels of spontaneous clearance, and non-responding patients had significantly higher ISG expression compared with subjects that achieved SVR after treatment.…”
Section: T He Current Study Comprehensively Evaluated the Prevalence mentioning
confidence: 99%
“…Patients with OCI have distinct clinical outcomes from those with CHC even of the same genotypes, indicating the role of host factors in OCI pathogenesis. The interleukin-28B (IL-28B) locus has been associated with HCV outcomes and IL-28B C/C was shown to occur more often in OCI than in CHC patients[ 19 ]. In OCI patients, intrahepatic HCV RNA load was significantly lower in those with the IL-28B C/C genotype than in those with C/T or T/T genotypes[ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The interleukin-28B (IL-28B) locus has been associated with HCV outcomes and IL-28B C/C was shown to occur more often in OCI than in CHC patients[ 19 ]. In OCI patients, intrahepatic HCV RNA load was significantly lower in those with the IL-28B C/C genotype than in those with C/T or T/T genotypes[ 19 ]. Thus, IL-28B polymorphisms may affect endogenous IFN-λ levels and be associated with low viral replication in some patients.…”
Section: Introductionmentioning
confidence: 99%